THE EFFECT OF COOPERATIVE SCRIPT (CS) ON STUDENTS’ READING COMPREHENSION AT MTSN 2 TANJUNG JABUNG TIMUR - Desti Angraini; Dwi Yunita (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
The aims of this research is to find out The Effect of Cooperative Script (CS) on Students’ Reading Comprehension at MTsN 2 Tanjung Jabung Timur. Moreover, the objective of this research is to find out significant difference between the students’ taught by Cooperative Scipt (CS) technique and those taught by teachers’ technique. This is quantitative research with quasiexperimental research design. The population and sample of this research is the students at the MTsN 2 Tanjung Jabung Timur. Which consist 22 students in experimental and 22 students in control class. The result of this research shows that there was significant effect on students’ reading comprehension after being taught through Cooperative Script (CS) technique. This could be seen from the T-test result which showed that the students mean score in experimental class 72,27 meanwhile the students mean score in control class 62,72. In the value sig. (2-tailed) was 0,002 which was lower than 0,05. The value of t0was 3,234 and df was 42. The t0 obtained is compared to t table either at 5%. At value 5% t table was 1,682. It can be analyzed that to is higher than t table either at level 5%. In other words, we can read 3,234 > 1,682. So the researcher can conclude that Ho is rejected and Ha is accepted. It means there was significant difference of reading comprehension between the students who were taught Cooperative Script (CS) technique and those who were not.